2022
DOI: 10.3390/nano12203573
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ternary Nanoparticles for Catalytic Ozonation to Treat Parabens: Mechanisms, Efficiency, and Effects on Ceratophyllum demersum L. and Eker Leiomyoma Tumor-3 Cells

Abstract: The use of parabens in personal care products can result in their leakage into water bodies, especially in public swimming pools with insufficient water treatment. We found that ferrite-based nanomaterials could catalytically enhance ozone efficiency through the production of reactive oxygen species. Our objective was to develop a catalytic ozonation system using ternary nanocomposites that could minimize the ozone supply while ensuring the treated water was acceptable for disposal into the environment. A tern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…The temporal monitoring of each paraben concentration revealed a rise in the observed pseudo first-order rate constant (k obs ), and %removal at 120 min in the order BP > PP > EP > MP (inset of Figure 2), which was due to the generated • OH, photoelectron (e − ), and • O 2 − , confirmed by our previously proposed radical formation mechanisms in our recent publication by Angkaew et al [12], which was similarly observed by other works [33,34]. The BP highest degradation efficiency was due to the BP molecular structure with a longer ester chain and the existence of more unsaturated C=C bonds, both of which were preferentially targeted by • OH and 35,36]. These results validate the occurrence of the reaction with • OH in a correlation with the alkyl chain length of the paraben [37].…”
Section: Paraben Degradation Efficiencysupporting
confidence: 82%
“…The temporal monitoring of each paraben concentration revealed a rise in the observed pseudo first-order rate constant (k obs ), and %removal at 120 min in the order BP > PP > EP > MP (inset of Figure 2), which was due to the generated • OH, photoelectron (e − ), and • O 2 − , confirmed by our previously proposed radical formation mechanisms in our recent publication by Angkaew et al [12], which was similarly observed by other works [33,34]. The BP highest degradation efficiency was due to the BP molecular structure with a longer ester chain and the existence of more unsaturated C=C bonds, both of which were preferentially targeted by • OH and 35,36]. These results validate the occurrence of the reaction with • OH in a correlation with the alkyl chain length of the paraben [37].…”
Section: Paraben Degradation Efficiencysupporting
confidence: 82%